VENTURE CAPITAL EFFECTIVENESS IN SMES AND STARTUPS: FINANCIAL INSTRUMENTS AND MARKET MECHANISMS - Muxitdinova Kamola Alisherovna (Modern American Journals, 2025)
This paper examines the effectiveness of venture capital (VC) for small and medium enterprises (SMEs) and startups through the lens of financial instruments and market mechanisms. The study integrates 2020–2024 evidence on VC deal dynamics, capital structures, exit pathways, portfolio risk management, and policy interventions across emerging and mature ecosystems. Using a mixed-methods design that combines quantitative benchmarking, portfolio analytics, and case-based evidence, we assess how instruments such as SAFE, convertible notes, preferred equity, revenue-based financing, and fund-of-funds I’000000000000000000000nfluence growth outcomes. Results indicate that instrument choice, governance discipline, and market depth jointly explain differences in survival, scaling, and exit performance. Implications are derived for entrepreneurs, fund managers, and policymakers in developing ecosystems.
Keywords: combines quantitative benchmarking, portfolio analytics, and case-based evidence